Cross-validation of IFN-γ Elispot assay for measuring alloreactive memory/effector T cell responses in renal transplant recipients. - Bestard, O; Crespo, E; Stein, M; Lúcia, M; Roelen, D; de Vaal, Y; Hernandez-Fuentes, M; Chatenoud, L; Wood, K; Claas, F; Cruzado, J; Grinyó, J; et al. (2013)
Assessment of donor-specific alloreactive memory/effector T cell responses using an IFN-γ Elispot assay has been suggested to be a novel immune-monitoring tool for evaluating the cellular immune risk in renal transplantation. Here, we report the cross-validation data of the IFN-γ Elispot assay performed within different European laboratories taking part of the EU RISET consortium. For this purpose, development of a standard operating procedure (SOP), comparisons of lectures of IFN-γ plates assessing intra- and interlaboratory assay variability of allogeneic or peptide stimuli in both healthy and kidney transplant individuals have been the main objectives. We show that the use of a same SOP and count-settings of the Elispot bioreader allow low coefficient variation between laboratories. Frozen and shipped samples display slightly lower detectable IFN-γ frequencies than fresh samples. Importantly, a close correlation between different laboratories is obtained when measuring high frequencies of antigen-specific primed/memory T cell alloresponses. Interestingly, significant high donor-specific alloreactive T cell responses can be similarly detected among different laboratories in kidney transplant patients displaying histological patterns of acute T cell mediated rejection. In conclusion, assessment of circulating alloreactive memory/effector T cells using an INF-γ Elispot assay can be accurately achieved using the same SOP, Elispot bioreader and experienced technicians in kidney transplantation.